(untitled) (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2024)
The 20th century is a very important period in the field of Bengali literature. A great change and instability has been observed in all social, political, or state spheres during this period. Since literature is the mirror of the society, contemporary reflection has happened in literature. Bengali poetry world is one of them. A special poet of this 20th century is Kazi Nazrul Islam. He started writing poetry free from the influence of Rabindra. One of the characteristics of his poetry is protest, rebellion. Also called rebel poet.